(untitled) (Journal of Parents and Teachers, 2014)
Robindranath Tagore was an Indian poet and philosopher of the nineteenth century. Its main theme is love for nature, which highlights it in most of his projects. He has written dozens of plays, poetry, novels, stories and painting works. Noteworthy that in the early twentieth century, founded his school Santiniketan which was based on the teachings of Eastern and Western philosophies, which also is betting on education for peace, ecological, environmental, related to democracy and solidarity other issues of great importance.